Artifícios retóricos como forma de sedução nas crônicas humorísticas de Carlos Eduardo Novaes e de Max Nunes - Almeida, Maria Cristina Máximo (2013)
This dissertation aims to answer whether there are specific techniques to cause humor in the chronicle genre. For such purpose, it analyzes, by means of rhetorical principles, the humorous chronicles: A Momolândia , by Max Nunes, and A Idade da Pedra , by Carlos Eduardo Novaes. At first, it draws on rhetorical studies to seek the ways to analyze the chosen samples, the argumentation data, and the elements that assist the persuasion process, including the argumentative operators, the figures, specially the rhetorical ones, and the types of arguments. In order to legitimize the rhetorical-argumentative analysis, it also comes to authors linked to Text Linguistics and Social Psychology. Regarding the presence of humor and its function in the chronicles, this dissertation uses the contribution of the following authors: ALBERTI (2011), BERGSON (2001), MINOIS (2003) who provide reflection on humor and laughter roles in the society starting from humorous techniques. Therefore, by associating argumentative techniques and specific characteristics of the humorous creation, it shows the way authors develop persuasive and convincing speeches. The selected chronicles emphasize the presence of the rhetoric as seduction and, although the authors practice different compositional styles and the chronicles have been written in distinct period, we can verify the predominance of similar rhetorical-humorous techniques, with small variations connected to the developed theme itself. In the analyzed chronicles, there are rhetorical figures of communion and choice, as metaphor and irony, which bring the speaker closer to the audience. The epidictic genre and the dialectical apodictic reasoning, which start from probable and true premises, prevail as well and, therefore, also bring the speaker closer to the audience. The analyzed authors make use of extrinsic evidences, to assure the veracity of the mentioned facts, and operators, especially the ones that present opposite conclusions. Regarding the argumentative constitution, we can verify the presence of incompatibility arguments, ridicule and dissociation. Concerning the intrinsic humor techniques, the incongruity and the transgressive character constitute the analyzed authors compositional tonic and present a relation to Social Psychology data, which is mentioned in the investigation. We conclude that the articulation in and between the parts of speech, inventio, dispositio, elocutio and actio, is the main responsible for the persuasion in different audiences. It is verified yet that the humorous chronicle genre is neither limited to promoting humor as an end in itself, nor it intends just to argue. It has indeed a transgressive character and aspires to raise the reality by means of comedy. The humor and the argumentation fuse into one speech and decimate their limits